A case of near miss maternal mortality - Sood, Akanksha; Kurdukar, D. V.; Daver, Rekha G.; Nagar, Vidya S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Eclampsia is a common cause of maternal morbidity and at times, mortality. Usually patients show dramatic improvement soon after delivery. But rarely eclampsia, dealt by obstetricians often, can herald an underlying life-threatening disease process requiring intensive care support and multi- disciplinary care. Such a case is being reported here.